PERAN MODERASI KUALITAS AUDIT DALAM PENGARUH FAKTOR INTERNAL DAN PENGHINDARAN PAJAK - Ningsih, Kurnia; Kusuma, Indra Cahya; Didi, Didi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research aims to explore how tax avoidance and audit quality, as moderating variables, are affected by sales growth, earnings management, and company age in consumer non-cyclical food and beverage subsector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The Cash Effective Tax Rate (CETR) is implemented in this current research to quantify tax avoidance. The addition of the quality of auditing variable serving as an interaction variable fills the research gap in this research.Methods: This analysis employed a quantitative descriptive methodology. The study's population consisted of 95 companies, and 30 companies, or 150 company data samples, were selected for the study through purposive sampling.Panel data regression and moderation regression (MRA) were employed in the data analysis, and the Eviews12 data processing program was used to test secondary data types.Results : . The results of this study suggest that sales growth and company age influence tax avoidance, whereas earnings management does not. The results of the moderation regression in this study indicate that audit quality cannot moderate the effect of sales growth and earnings management on tax avoidance, while audit quality can moderate and weaken the impact of company age on tax avoidance.Conclusion and suggestions: Suggestions for future researchers include expanding the sample size, increasing the research period, and exploring additional independent variables, as well as selecting different company sectors. This will provide the public and potential investors with a more comprehensive understanding when making investment decisions. Keywords: Audit Quality, Company Age, Earnings Management, Sales Growth, and Tax Avoidance.